A new classification proposal of judo throwing techniques : A pilot study - Almansba, R.; Sterkowicz, S.; Calmet, M.; Ahmaidi, S. (6th EJU Exhibition of Judo Research & 2nd European Science of Judo Research Symposium.,16 May 2015., 2015)
This study aims to establish a new classification of judo techniques based on physiological criteria. Sixteen French high-level judokas (age =18 ± 3 years and body mass (BM) =74 ± 6 kg) participated in this research. The explosive power, force and velocity were assessed during the force/velocity test (FVT). Forty eight hours following the FVT, each participant carried out 3 trials of Nage komi (NK) to ascertain of the throwing performance. Each trial composed of 15s of Osoto-gari (OSG), 15s of Uchi mata (UMA) and 15s of Ippon Seoi-nage (ISN).Three minute of passive recovery were given between each set and 10-min between each trial. All participants were videotaped to accurately estimate the number of throws. The order of technical execution was randomized. The maximal number of repetitions for each technique during the 3 trials was considered for analysis. The FVT results were: F0/BM=0.23 ± 0.01 N.kg-1, V0=230 ± 7 rev.min-1, Pmax/BM=13.30 ± 1.1 W.kg-1 and final HR- FVT=167 ± 7 beats.min-1.The throws number accomplished during NK were: ISN=12 ± 1 reps, OSG=11 ± 1.0 reps and UMA=11 ± 1 reps and final HR-NK=182 ± 6 beat.min-1. Higher correlations were found between ISN throwing number (ISNTN) and velocity (r=0.66, p<0.01), ISNTN and explosive power (0.67, p<0.01) and between total throwing number with velocity (r=0.76, p<0.01). However, only the velocity was correlated with OSGTN and UMATN. (r=0.58 and 0.53 respectively, p<0.05). Paradoxically, no correlation has been shown between the 3 experimented throwing techniques. Our findings highlighted that the ISN technique associates significantly both velocity and explosive power while OSG and UMA involve more velocity. These point out that the 3 techniques do not belong to the same physiological register. The new classification proposed is more rational than the Kodokan classification and provides practical knowledge could be applied by coaches to prescribe specific throwing techniques corresponding to the physiological profile of judoka Available from: https://www.researchgate.net/publication/276266821_A_New_Classification_proposal_of_Judo_throwing_techniques__A_PIlot_Study